Advances in the Conceptualization of the Stress Process
XIV, 261 p.
Keywords: The stress process paradigm has been one of the most dominant conceptual models of health and illness over the past three decades. The contributions to this volume chart a new course for the stress process, extending the paradigm conceptually, methodologically, and substantively. Written in honor of Leonard I. Pearlin, the leading proponent of the stress process, the contributions to this volume provide a new direction for stress process research. Featuring contributions from leading researchers, and an afterword by Leonard I. Pearlin, this comprehensive volume covers three major sections: -Conceptual and methodological extensions of the stress process -The roles of family and work in the stress process, throughout the life course - Psychosocial factors that impact health outcomes This volume will be an invaluable resource for researchers in sociology, social psychology and public health, all seeking to understand the pervasive role of stress on social disparities in health and illness.